OMA1 competitively binds to HSPA9 to promote mitophagy and activate the cGAS–STING pathway to mediate GBM immune escape - Lin Li; Rong Fu; Wen de Zhu; Jin Rao; Li hua Zhang; Ka ming Xue; Jun jun Li; Qian zhi Chen (Journal for ImmunoTherapy of Cancer, 2024)
Background Immunotherapy with checkpoint inhibitors, especially those targeting programmed death receptor 1 (PD-1)/PD-1 ligand (PD-L1), is increasingly recognized as a highly promising therapeutic modality for malignancies. Nevertheless, the efficiency of immune checkpoint blockade therapy in treating glioblastoma (GBM) is constrained. Hence, it is imperative to expand our comprehension of the molecular mechanisms behind GBM immune escape (IE).Methods Protein chip analysis was performed to screen aberrantly expressed OMA1 protein in PD-1 inhibitor sensitive or resistant GBM. Herein, public databases and bioinformatics analysis were employed to investigate the OMA1 and PD-L1 relation. Then, this predicted relation was verified in primary GBM cell lines through distinct experimental methods. To investigate the molecular mechanism behind OMA1 in immunosuppression, a series of experimental methods were employed, including Western blotting, co-immunoprecipitation (Co-IP), mass spectrometry (MS), immunofluorescence, immunohistochemistry, and qRT-PCR.Results Our findings revealed that OMA1 competitively binds to HSPA9 to induce mitophagy and mediates the IE of GBM. Data from TCGA indicated a significant correlation between OMA1 and immunosuppression. OMA1 promoted PD-L1 levels in primary cells from patients with GBM. Next, the results of Co-IP and MS conducted on GBM primary cells revealed that OMA1 interacts with HSPA9 and induces mitophagy. OMA1 promoted not only cGAS–STING activity by increasing mitochondrial DNA release but also PD-L1 transcription by activating cGAS–STING. Eventually, OMA1 has been found to induce immune evasion in GBM through its regulation of PD-1 binding and PD-L1 mediated T cell cytotoxicity.Conclusions The OMA1/HSPA9/cGAS/PD-L1 axis is elucidated in our study as a newly identified immune therapeutic target in GBM.